1999
DOI: 10.1088/0960-1317/10/1/301
|View full text |Cite
|
Sign up to set email alerts
|

Electro-discharge machining of mesoscopic parts with electroplated copper and hot-pressed silver tungsten electrodes

Abstract: Recent advances in the development of plasma etchers for silicon has brought machines to the market which are able to etch silicon with high etch rates (>5 µm min −1) at high anisotropy (taper of sidewalls <1.5 •). Micromachined silicon is therefore not only suitable for applications in micromechanics but it can also fill the gap which exists between conventional macromachining (milling, turning) with feature sizes usually >1 mm and microelectromechanical systems with feature sizes <100 µm. In this work microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Electrical and thermal properties were excellent according to the authors, as was also the wear resistance of the electrodes. Stampfl et al [95] described a new method for producing copper-tungsten, where silicon is used as a mold for electroplating copper-tungsten. The authors reported that the electrodes made by this method are suitable to shape any kind of conductive material, especially amorphous metal, which are difficult to machine with conventional methods.…”
Section: Edm Of Metals and Their Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical and thermal properties were excellent according to the authors, as was also the wear resistance of the electrodes. Stampfl et al [95] described a new method for producing copper-tungsten, where silicon is used as a mold for electroplating copper-tungsten. The authors reported that the electrodes made by this method are suitable to shape any kind of conductive material, especially amorphous metal, which are difficult to machine with conventional methods.…”
Section: Edm Of Metals and Their Alloysmentioning
confidence: 99%
“…As described above, Stampfl et al [95] described a new method for producing silver-tungsten electrodes, where silicon is used as a mold for hot pressing silver-tungsten. Similar results as those with copper-tungsten electrodes were achieved.…”
Section: Silver Tungsten (Agw)mentioning
confidence: 99%
“…The EDM process eradicates material through originating controlled sparks between an electrically conductive work piece and a shaped electrode. In the EDM process an electric spark is used to cut the workpiece, which takes the shape opposite to that of the cutting tool or electrode (Stampfl et al, 2000). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Wire electrodes as thin as 25 µm are used with advanced spark control limiting the 'overburn', the gap between tool electrode and work piece, to as little as 3 µm. The micro-EDM process has been used for fabrication of meso-scale parts of dimensions 10 µm to 100 µm from difficult-to-machine materials including hardened tool steel, titanium, tungsten, diamond, doped silicon, gallium arsenide and rare earth magnetic materials [3,4].…”
Section: Introductionmentioning
confidence: 99%